2021
DOI: 10.1021/acs.jpcb.1c00664
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Binary Surfactant Mixtures in Two-Phase and Three-Phase Systems

Abstract: Cationic alkyltrimethylammonium bromides (C n TAB, with n = 8, 12, 16, 18) and their mixtures with n -octanol as a nonionic surfactant were chosen as a model system to study the synergistic effect on foamability (two-phase system) and floatability (three-phase system) of quartz in the presence of binary mixtures of ionic/nonionic surfactants. The foam height of one-component solutions and binary mixtures and floatability of quartz particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
1
9
1
Order By: Relevance
“…This is consistent with the fact that CTAB adsorption results in a better neutralization of the water/PO interface charge, with respect to SDS adsorption, that is also reflected by a different stability of the corresponding emulsions. These results are also consistent with previous studies that reported about the synergistic interactions between non-ionic and cationic surfactants. For instance, the adsorption of CTAB was enhanced due to the synergies between CTAB and TX-100 (Triton X-100, a non-ionic surfactant) . A similar behavior was also reported for the surfactant mixture of DDAB (didodecyldimethylammonium bromide, a cationic surfactant) and Igepal CO-890 (polyoxyethylene-40 nonylphenyl ether, a non-ionic surfactant) in oil-in-water emulsions .…”
Section: Resultssupporting
confidence: 92%
“…This is consistent with the fact that CTAB adsorption results in a better neutralization of the water/PO interface charge, with respect to SDS adsorption, that is also reflected by a different stability of the corresponding emulsions. These results are also consistent with previous studies that reported about the synergistic interactions between non-ionic and cationic surfactants. For instance, the adsorption of CTAB was enhanced due to the synergies between CTAB and TX-100 (Triton X-100, a non-ionic surfactant) . A similar behavior was also reported for the surfactant mixture of DDAB (didodecyldimethylammonium bromide, a cationic surfactant) and Igepal CO-890 (polyoxyethylene-40 nonylphenyl ether, a non-ionic surfactant) in oil-in-water emulsions .…”
Section: Resultssupporting
confidence: 92%
“…28 Wiertel-Pochopien et al proposed the mechanism of synergistic effect in mixed C n TAB−C 8 OH solutions in two-phase and threephase systems, and the discussion was supported by MD simulations. 29 However, MD simulation with rheology and small-angle neutron scattering (SANS) studies have scarcely concentrated on the quantitative effect of C 8 OH on CTAB micelles. Thus, our study aims to scrutinize the influence of long-chain alcohol, viz., C 8 OH, on tuning the micellar morphology of CTAB, giving an account of the phase behavior, rheology, and SANS measurements.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition to the experimental approach, theoretical studies have also offered a better understanding of surfactant solutions expressed in terms of interfacial properties and structural transitions in the presence of alcohols at the atomistic level over the last decade. , However, the molecular dynamics (MD) simulation approach in this direction is still not explored widely. , The MD carried out on cationic surfactant in the presence of alcohols is thought to be the most straightforward method. , Verma et al performed the atomistic-level study of cetylpyridinium bromide (CPB) surfactant by MD simulations, which was then verified by investigating its structural and dynamic properties in water, C 8 OH, and micelle . Jia et al examined the shape and structural evolution of preassembled cylindrical CTAB micelles in the presence of C 8 OH by MD simulations .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it was concluded that some micelle demixing is occurring between the gemini and the zwittergent under certain micellar composition ranges, a phenomenon rarely associated with hydrocarbon surfactants. Again, Tan et al synthesized novel "linear" trisiloxane surfactants with different terminal groups (CH 3 −, ClCH 2 −, CF 3 −) and two polyether hydrophilic groups followed by successful characterization using the 1 H NMR, 13 C NMR, 29 Si NMR, and FTIR spectroscopy. 8 In addition to this, the aggregation and adsorption behaviors of these surfactants in aqueous solution were studied by surface tension, dynamic light scattering (DLS), and transmission electron microscopy (TEM).…”
mentioning
confidence: 99%